TRAINING AND RETRAINING OF PSYCHO-PEDAGOGICAL STAFF AT A REGIONAL UNIVERSITY - Natalia V. Shklyar (Высшее образование в России)
The article deals with continuing education in the process of psycho-pedagogical training and retraining in the system of multi-level professional development. Offers basic conceptual and content aspects of the formation and improvement of professional competencies of the students of PGU named after Sholom-Aleichem in academic, extra-curricular (educational) work, while passing through various practices. Programmes for teachers’ retraining in postgraduate education include four basic modules: (1) “The main trends and the modern priorities in education”, (2) “The topical issues of learning and education. The innovative technologies in education”, (3) “Psychological studies of children and schoolchildren, remediation and prevention measures”, (4) “Methodical aspects of learning process organization”.